Memperbaiki Ekonomi Desa Pangarungan Pasca Pandemi Covid-10 Melalui Usaha Kecil Menengah (UKM) - Nadia Ika Purnama; Fauzan Habibi (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
Pangarungan village is one of the sub-districts located in Torgamba sub-district, Labuhan Batu district, south of North Sumatra Province with an area of 12,393Ha. Village potential is all natural resources and human resources owned by the village as the basic capital that needs to be managed and developed for the survival of the village. The needs contained in the potential for education in the village of Pangarungan are the lack of mastery of the use of technology in the learning process and facilities are also still minimal, the need for industrial potential, namely, the lack of marketing capabilities for industrial products (SMEs) so that the distribution of products outside the region is still minimal and results in no increase in production in the field industry. The need for agricultural potential is normal soil nutrients, but micro nutrients are still very lacking. Therefore, PkM implementers can assist the community to be motivated to optimize agricultural products. The community can develop local potential and community creativity. People can be innovated to live clean, healthy and have a high spirit of cooperation